2009
DOI: 10.1007/s12094-009-0319-9
|View full text |Cite
|
Sign up to set email alerts
|

Professional burnout among Spanish medical oncologists

Abstract: The results suggest the importance of developing prevention and intervention lines for medical oncology burnout. In this sense, issues such as work time management and motivational aspects related to research tasks could be worth considering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(9 reference statements)
0
1
1
4
Order By: Relevance
“…This result is in contrast to the survey of the Spanish Society of Medical Oncology [15], which showed the perception of time pressure and social deterioration to be responsible for high burnout levels. Shanafelt et al [16] found that, among the North Central Cancer Treatment Group (NCCTG) for medical oncologists, ‘patient load', followed by ‘balancing personal and professional life' and ‘dealing with death/suffering of patients' were the main stressors.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in contrast to the survey of the Spanish Society of Medical Oncology [15], which showed the perception of time pressure and social deterioration to be responsible for high burnout levels. Shanafelt et al [16] found that, among the North Central Cancer Treatment Group (NCCTG) for medical oncologists, ‘patient load', followed by ‘balancing personal and professional life' and ‘dealing with death/suffering of patients' were the main stressors.…”
Section: Discussioncontrasting
confidence: 99%
“…This situation can be a source of high-leveled stress to the managing team. [14] Other sources of burnout in the health sector can be linked to seniority and workplace factors as can be seen among nurses and other cadre of health care staff. [15] Individual factors that may contribute to burnout include demographic variables (age, marital status, and educational level); personality traits (low hardiness and poor self-esteem); and job attitudes (unrealistically high expectations, poor salary).…”
Section: Introductionmentioning
confidence: 99%
“…Éste fenómeno ha sido identificado en muchos profesionales de la salud (Felton, 1998), incluida el área de la medicina oncológica, donde se ha encontrado una alta prevalencia (Camps et al, 2009;Whippen y Canellos, 1991). La costosa tarea de trabajar con pacientes enfermos y sus familiares y trabajar con asuntos emocionalmente complicados, hacen que los retos que asumen diariamente estos profesionales se conviertan en factores de riesgo que pueden predisponer a la aparición del desgaste profesional (Trufelli et al, 2008;Moriana, 2006).…”
Section: Introductionunclassified